The systemic approach to the formation of preschool administrators’ perceptions about the psychological safety of the educational environment - Maria D. Kukushkina (Современное дошкольное образование)
Background. Social perceptions of the administrators of educational institutions about the psychological characteristics of the educational environment are a key factor influencing the effectiveness of the system of interaction in the team. The organizational and managerial component of the educational environment is of primary importance in the formation of a psychologically safe kindergarten educational environment that promotes the maintenance of the emotional well-being of all its subjects.